Perancangan Aplikasi Sistem Informasi Akuntansi Penjualan Menggunakan Software Microsoft Access 2016 (Studi Kasus Toko Diecolz85) - Yanuar Muhammad Nazar; Rendra Trisyanto Surya (Indonesian Accounting Literacy Journal, 2021)
"Diecolz85" store is a business in the field of selling SME-scale furniture items at the level of small businesses. In carrying out its operational activities, the store still implements a sales recording system manually on an ordinary notebook, and there is a lack of sensitivity to the importance of good financial records, so it becomes a problem that needs to be resolved, the owner wants good records, where data processing is fast, data accuracy and reliability very emphasized so that it can expedite daily operational activities. Therefore, as a form of solution to this problem, the authors designed an application program according to the needs and desires of the store, using the SLDC method and designing an application program. The author uses Microsoft Access 2016 software to solve the problems that exist in the Accounting Information System for the Sale of Furniture Goods in the "Diecolz85" Store.